The Function of CBM32 in Alginate Lyase VxAly7B on the Activity on Both Soluble Sodium Alginate and Alginate Gel - Tang, Luyao; Guo, Enwen; Zhang, Lan; Wang, Ying; Gao, Shan; Bao, Mengmeng; Han, Feng; Yu, Wengong (Frontiers in Microbiology, 2022)
Carbohydrate-binding modules (CBMs), as an important auxiliary module, play a key role in degrading soluble alginate by alginate lyase, but the function on alginate gel has not been elucidated. Recently, we reported alginate lyase VxAly7B containing a CBM32 and a polysaccharide lyase family 7 (PL7). To investigate the specific function of CBM32, we characterized the full-length alginate lyase VxAly7B (VxAly7B-FL) and truncated mutants VxAly7B-CM (PL7) and VxAly7B-CBM (CBM32). Both VxAly7B-FL and native VxAly7B can spontaneously cleavage between CBM32 and PL7. The substrate-binding capacity and activity of VxAly7B-CM to soluble alginate were 0.86-fold and 1.97-fold those of VxAly7B-FL, respectively. Moreover, CBM32 could accelerate the expansion and cleavage of alginate gel beads, and the degradation rate of VxAly7B-FL to alginate gel beads was 3-fold that of VxAly7B-CM. Results showed that CBM32 is not conducive to the degradation of soluble alginate by VxAly7B but is helpful for binding and degradation of insoluble alginate gel. This study provides new insights into the function of CBM32 on alginate gel, which may inspire the application strategy of CBMs in insoluble substrates.